Quechua poetry: kidnapped writing and contemporary corpus (XX and XXI centuries) - Espino Relucé, Gonzalo (2019)
We understand contemporary Quechua poetry as the establishment of resistance culture. Its validity as written language occurs through the twentieth century and strengthens in the twenty-first century. As a text type made in an entanglement of Quechua tradition with learning impressions of Western culture, we examine how and which criteria could be used to address a corpus of contemporary Quechua written poetry. We reviewed this approach from a perspective of kidnapped writing, considering notions as literary process, literary writing, and literary zone. We worked with sources from 1904 to 2017.